Gender Equity in Land and Forest Tenure in REDD+ Programming - World Bank (Washington, DC: World Bank, 2022)
The purpose of this study is to understand the legal and policy constraints and opportunities in each of the 17-carbon fund (CF) countries affecting women’s land and forest tenure. The study also explores women’s ability to exercise land and forest rights in statutory and customary systems; how these rights may be affected by the CF programs (ERPs and BSPs); as well as what is needed to further protect and strengthen women’s rights to land and forest tenure along with their ability to govern in the CF countries. This synthesis report provides a big-picture overview of the findings from all the studies; additional and more detailed information related to the activities in each country is available in the 10 country scans and seven deep-dive country reports. Because this report is a synthesis of findings from 17 countries, all statements taken from other sources are cited in the country studies. Furthermore, a bibliography of sources can be found at the end of this synthesis report.